Arginine Vasopressin Effects on Subjective Judgments and Neural Responses to Same and Other-Sex Faces in Men and Women - Rilling, James K.; Li, Ting; Chen, Xiangchuan; Gautam, Pritam; Haroon, Ebrahim; Thompson, Richmond R. (Frontiers in Endocrinology, 2017)
Arginine vasopressin (AVP) influences social and emotional behaviors across a wide range of species. In humans, intranasal AVP has been previously shown to alter physiological responses to and subjective judgements of same-sex faces in both men and women. The present study attempted to elucidate the neural mechanism for these effects by randomizing 40 healthy men and 40 healthy women to treatment with either 40 IU intranasal AVP or a saline placebo approximately 30 minutes before imaging their brain function with fMRI as they viewed same and other-sex faces. All subjects were also scanned a second time several days later with no treatment to evaluate the persistence of AVP effects over time. AVP acutely increased positive ratings of same-sex faces in women, with some evidence that these effects persisted until the second scan. While AVP had no acute effects on same-sex ratings in men, AVP increased positive ratings of same-sex faces several days later. On the other hand, AVP had no effect on other-sex face judgements in either sex. AVP modulation of brain function was focused on the nucleus accumbens (NAc) and the lateral septum, two reward processing areas involved in the formation of social bonds. AVP provoked acute increases in right NAc and bilateral lateral septum responses to female faces among men, with left lateral septum responses persisting over time while right NAc responses reversed over time. Finally, AVP modulated hypothalamic activation to faces in both men and women. The present study therefore indicates that intranasal AVP affects subjective ratings and neural responses to same and other-sex faces in men and women, with some effects persisting and others emerging over time. Future studies should investigate whether AVP effects are modulated by individual variables such as genotype, personality or attachment style as previously reported for nonapeptides.